An Analysis of the Influence of Mother Tongue on English Pronunciation: A Case Study of EFL Learners at Bakong Pitthaya School, Thailand - Nor Aeni Indah Kurniasari; Niken Kencono Ungu (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the impact of Thai students' first language (L1) on their English pronunciation within the context of English as a Foreign Language (EFL) at Bakong Pitthaya School in Thailand. The researcher used a descriptive qualitative method design on a case study with Contrastive Analysis Theory on English pronunciation. Recorded interviews and pronunciation testing were the main techniques of data collection instruments. The subjects of this research were secondary grade students of Bakong Pitthaya School Pattani, Thailand. The results of this study aimed to provide actionable recommendations for the teachers to enhance pronunciation instruction and improve student pronunciation skill. This research contributes to the understanding of L1 influence on L2 pronunciation, offering insights that can inform teaching practices in similar EFL contexts.